2016
DOI: 10.1016/j.jacr.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

White Paper on P4 Concepts for Pediatric Imaging

Abstract: Over the past decade, innovations in the field of pediatric imaging have been largely based on single center and retrospective studies, which provided limited advances for the benefit of pediatric patients. In order to identify opportunities for potential quantum leap progress to the field of Pediatric Imaging, the American College of Radiology - Pediatric Imaging Research (ACR - PIR) Committee has identified high impact research directions related to the P4 Concept of Predictive, Preventive, Personalized, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
6
0
2
Order By: Relevance
“…As such, there has been a recent interest in the utility of three‐dimensional (3D) imaging for this population. This has been further amplified by White Paper publications and establishment of guidelines by both the American College of Radiology and the Radiological Society of North America 7,8 . While magnetic resonance imaging (MRI) and computed tomography (CT) have been the foundation of preoperative oncologic imaging, 4 incorporating 3D modeling and printing for enhanced visualization appears beneficial 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, there has been a recent interest in the utility of three‐dimensional (3D) imaging for this population. This has been further amplified by White Paper publications and establishment of guidelines by both the American College of Radiology and the Radiological Society of North America 7,8 . While magnetic resonance imaging (MRI) and computed tomography (CT) have been the foundation of preoperative oncologic imaging, 4 incorporating 3D modeling and printing for enhanced visualization appears beneficial 9 …”
Section: Introductionmentioning
confidence: 99%
“…This has been further amplified by White Paper publications and establishment of guidelines by both the American College of Radiology and the Radiological Society of North America. 7,8 While magnetic resonance imaging (MRI) and computed tomography (CT) have been the foundation of preoperative oncologic imaging, 4 incorporating 3D modeling and printing for enhanced visualization appears beneficial. 9 Specifically, within pediatric oncology, previous work has suggested that 3D printing may be useful for complex tumor resections, 10,11 though these techniques have yet to be published within the United…”
Section: Introductionmentioning
confidence: 99%
“…Several of these initiatives (particularly dose reduction and optimisation, data registries and improving image analysis) are shared with other paediatric imaging representatives, such as the Paediatric Imaging Research Committee of the American College of Radiology (White paper [41]) and we look forward to joint initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Zukunftsweisende Konzepte zielen darauf ab, die Akzeptanz der MRT-Untersuchung zu verbessern und die Methodik für ein erweitertes Indikationsspektrum mit konkreten, klinisch relevanten Endpunkten zu etablieren [8]. Mithilfe einer Kombination aus pädagogisch-spielerischen Ansätzen und neuen MRT-Techniken lässt sich das Risikoprofil der MRT verbessern und hierdurch die Notwendigkeit einer Sedierung und die Verwendung von Gadolinium-haltigen Kontrastmitteln minimieren.…”
Section: Mrt-techniken Der Zukunft In Der Pädiatrischen Radiologieunclassified
“…Diese Anwendung könnte z. B. für die nichtinvasive Überwachung der Oxygenierung des Gehirns und der Viszeral-Organe bei Frühgeborenen eingesetzt werden[8].Positronen-Emissionstomografie (PET) und PET/CT PET und PET/CT sind seit vielen Jahren für die molekulare Bildgebung von pädiatrischen Tumoren etabliert [55]. Zu den Vorteilen gehören die hohe Empfindlichkeit (Erkennung von Pikomolar-Konzentrationen) und ein hoher Tumor-zu-Hintergrund-Kontrast.…”
unclassified